2011
DOI: 10.1007/s11665-011-9871-x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Processing Map for 7075 Al/20% SiCp Composite

Abstract: The hot deformation behavior and microstructure evolution of 7075 Al/20% SiC p composite have been studied using the processing map. Compression tests were carried out in the temperature range of 300-500°C and at the strain rate range of 0.001-1.0 s 21 . The stable and unstable regions in the map were verified with the microstructural observations of the deformed compression specimens. The ''stable'' regions, i.e., dynamic recrystallization and ''unstable'' regions such as debonding of SiC particles, matrix cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…Based on the dynamic material model (DMM), the processing maps were developed by Prasad et al [17]. In recent years, the processing map has been extensively accepted as a powerful tool for optimizing the hot working parameters and controlling the microstructures of metals and alloys [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Li et al [18] established 3D processing maps for the extruded ZK60 magnesium alloy and determined two feasible hot working domains, i.e., the DRX and superplasticity domains.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the dynamic material model (DMM), the processing maps were developed by Prasad et al [17]. In recent years, the processing map has been extensively accepted as a powerful tool for optimizing the hot working parameters and controlling the microstructures of metals and alloys [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Li et al [18] established 3D processing maps for the extruded ZK60 magnesium alloy and determined two feasible hot working domains, i.e., the DRX and superplasticity domains.…”
Section: Introductionmentioning
confidence: 99%
“…EI Mehtedi et al [29] analyzed the hot workability of GC15 steel by torsion tests under the temperature range of 1125-1000 1C and strain rate range of 0.005-5 s À 1 . Rajamuthamilselvan and Ramanathan [30], Liu et al [31], Senthilkumar et al [32] and Han et al [33] developed the processing maps for 7075 Al/20% SiCp composite, as-cast 6Mo superaustenitic stainless steel, Al-based nanocomposite and 20Cr-25Ni superaustenitic stainless steel, respectively, and the optimized processing parameters were obtained. Samantaray et al [34,35] studied intrinsic workability of the modified 9Cr-1Mo steel and a nitrogen enhanced 316L(N) stainless steel by processing maps, and the relationship between microstructure and hot workability were investigated through microstructural observations.…”
Section: Introductionmentioning
confidence: 99%
“…Several methods, such as stir casting technique [10e13] , powder metallurgy [14e16] spraying process [17,18] , friction stir welding [19,20] and squeeze casting [21] , have been used to prepare SiC p /7xxxAl composites. Rajamuthamilselvan et al [10,11] investigated the hot deformation behavior of 15 and 20 vol.% SiC p /7075Al composites prepared by stir casting, and found that the composites demonstrated higher flow stress, efficiency and lower instability regimes than 7075 alloy. Izadi et al [14] found that the hardness of 4e16 vol.% SiC p /7075Al composites fabricated by powder metallurgy method was at least 22% higher than that of Al alloy.…”
Section: Introductionmentioning
confidence: 99%
“…Since the DMM model and instability criterion have been proposed, the thermal processing diagram has been widely used in the field of material formability. Rajamuthamilselvan et al [12] obtained the best hot working parameters of material by observing and analysing the microstructure of various regions in a hot processing map of 7075 aluminum alloy. Dharmendra et al [13] constructed a thermal processing map of TX32 magnesium alloy.…”
Section: Introductionmentioning
confidence: 99%